Assessment and Control of Radiation Doses in X-Ray Rooms of Treatment and Prevention Institutions of Khorazm Region (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Background. The radiation safety system includes a set of measures aimed primarily at comprehensive reduction of radiation doses for the population belonging to category "A" (employees), that is, for persons in professional contact with radiation sources. In accordance with the requirements of the International Commission on Radiation Protection (ICRC), individual radiation doses should be monitored for all persons in this group to ensure that radiation does not exceed the established dose limit (20 mZv/year).Material and methods. The ionizing radiation dose rate was measured at the workplaces of the X-ray rooms of the treatment and prevention institutions (TPI) in the Khorezm region, as well as the annual personal radiation doses were studied. The number of medical facilities using SIRs in Khorezm region is 54, and the total number of equipment using SIRs is 125. Measurements were made with a DRG-107C device. We estimated the value of radiation doses according to Radiation safety standards (RSS-2006) according to Sanitary standards and rules (SanNandR -2006).Results. According to the obtained results, it was found that the highest average indicator is behind the small curtain of object  1 (0,37 mkZv/hour), and the lowest average indicator is in front of the back wall of object  4 (0,15 mkZv/hour). The results of measuring the radiation dose power at the workplaces of employees, included in category "A", showed that the level of X-ray radiation in most points did not exceed the level of radiation dose stipulated in SanNandR 0194-06 "Hygienic requirements for installation and operation of X-ray rooms, equipment and conducting X-ray studies".Conclusion. The results obtained allow us to characterize the working conditions of category “A” workers in X-ray rooms in the Khorezm region as favorable.